Mortality in the Volgograd Region Against the COVID-19 Pandemic - A. V. Alpatov (Статистика и экономика, 2022)
The COVID-19 pandemic, which began in Russia in March 2020, had a huge impact on socio-economic processes. In numerous studies analyzing mortality caused by coronavirus infection, it is concluded that the number of deaths is underestimated. The high morbidity and mortality caused by coronavirus infection has far-reaching consequences for the economy of the regions and the country as a whole: deterioration in health, a decrease in the working-age population, a change in the structure of consumption of goods and services, etc. In this regard, it is relevant to analyze the processes associated with mortality from coronavirus infection.The purpose of the study is to identify the main trends in the nosological and age-sex structure of mortality in the Volgograd region in the years preceding the COVID-19 pandemic, to assess the contribution of mortality from coronavirus infection to total mortality in 2020. Estimation of excess mortality was carried out taking into account the dynamics of age-specific mortality rates.Materials and methods. The main sources of information for the study of mortality were the Russian database on fertility and mortality and Rosstat data. In the work, when analyzing mortality from COVID-19, data from the operational headquarters were also used. The analysis of the mortality dynamics was carried out using such indicators as the average life expectancy at birth, the crude death-rate, age-specific mortality rates in absolute and  relative (per 1000 people) terms. The processing of statistical data was carried out using the Microsoft Excel application package and matplotlib, pandas, numpy (Python programming language), pyramid (R programming language) libraries.Results. In 2020, the number of deaths in the Volgograd region turned out to be more than in 2019 by 6647 people. If the trends in the dynamics of the intensity of mortality would persist in the year of the pandemic, then the total number of deaths in the Volgograd region would be equal to 32044 people. In this case, the excess mortality would have amounted to 7368 people.Conclusion. As a result of the study, it was revealed that a significant increase in the number of deaths in the Volgograd region during the pandemic is explained by Rosstat as the cause of coronavirus infection by only 33.2%. This discrepancy may be the result of incorrect accounting of deaths from coronavirus infection. Another factor in the increase in mortality during a pandemic may be a decrease in the quality of medical care. There has been a reorientation of the work of medical institutions to the treatment of patients with coronavirus infection; the burden on emergency medical care has increased.